2009
DOI: 10.1021/pr8008385
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Serum Glycomics of Esophageal Adenocarcinoma and Other Esophageal Disease Onsets

Abstract: Aberrant glycosylation has been implicated in various types of cancers and changes in glycosylation may be associated with signaling pathways during malignant transformation. Glycomic profiling of blood serum, in which cancer cell proteins or their fragments with altered glycosylation patterns are shed, could reveal the altered glycosylation. We performed glycomic profiling of serum from patients with no known disease (N=18), patients with high grade dysplasia (HGD, N=11) and Barrett’s (N=5), and patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 37 publications
1
82
0
1
Order By: Relevance
“…Mechref et al performed glycosylation profiling of serum samples from patients with EAC, high-grade dysplasia, Barrett's esophagus, and healthy individuals and showed that the changes in the relative intensities of three glycan structures predicted EAC with 94% sensitivity and more than 60% specificity [39], suggesting that comparative EAC glycomics can be used for the identification of EAC candidate biomarkers.…”
Section: Eacmentioning
confidence: 99%
“…Mechref et al performed glycosylation profiling of serum samples from patients with EAC, high-grade dysplasia, Barrett's esophagus, and healthy individuals and showed that the changes in the relative intensities of three glycan structures predicted EAC with 94% sensitivity and more than 60% specificity [39], suggesting that comparative EAC glycomics can be used for the identification of EAC candidate biomarkers.…”
Section: Eacmentioning
confidence: 99%
“…They identified 98 glycan features with different intensities in disease onsets and 26 of them correspond to known glycan structures. They showed statistically significant glycan changes between 4 different conditions (Healthy/BE/HGD/EAC) with 3 of the known potential N-glycan biomarkers predicting EAC with 94% sensitivity and 60% specificity (135). Another study used microchip electrophoresis with laser-induced fluorescence detection for N-glycan profiling and were able to differentiate between the healthy, Barrett's esophagus, HGD, and EAC conditions (136).…”
Section: Glycan Profilingmentioning
confidence: 99%
“…1, shaded grey), that differs from the other families in having no core fucosylation. The human plasma glycome is characterized by the absence of core fucose plus high levels of 2-6 sialylation (13,14). Therefore we concluded that this fourth glycan family was largely derived from the follicular fluid constituents that co-purify with ZP (Table S1).…”
mentioning
confidence: 93%